2018
DOI: 10.4172/2329-8731.1000183
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Extended Spectrum Beta-Lactamase-Producing Uropathogens among UTI Patients in the Governmental Hospitals of North West Bank: A Cross-Sectional Study

Abstract: Background: Urinary tract infections caused by Extended Spectrum Beta-Lactamase producing organisms (UTI-ESBL) are increasing in incidence and pose a great threat to modern medicine. The objective of this study was to assess the prevalence and risk factors of Extended Spectrum Beta-Lactamase (ESBL)-producing uropathogens among patients with urinary tract infections in the north of West Bank and to determine the antimicrobial susceptibility profile of the isolated bacteria. Methods: A total of 427 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
3
3
Order By: Relevance
“…[35][36][37] . In contrast, several studies reported the highest ESBL production among K. pneumoniae followed by E. coli which do not match our results [38][39][40] , since we found E. coli as the predominant ESBL producer.…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%
“…[35][36][37] . In contrast, several studies reported the highest ESBL production among K. pneumoniae followed by E. coli which do not match our results [38][39][40] , since we found E. coli as the predominant ESBL producer.…”
Section: Percent Of Sensiɵvitycontrasting
confidence: 99%
“…K. pneumoniae was the dominant extended-spectrum β-lactamase (ESBL) producing organism, accounting for 58.1% of cases, followed by E. coli at 54%. These are slightly higher numbers than previously reported in our region in 2018 21 where E. coli accounted for 42.5%, K. pneumoniae for 54.9% , and P. mirabilis for 7.14%. Given the high rates of ESBL production in E. coli and K. pneumoniae , it was not surprising to observe high resistance rates to cephalosporins and ampicillin.…”
Section: Discussioncontrasting
confidence: 68%
“…The rate of ESßL production was greater in K. pneumoniae (76.6 percent) than in E. coli (68.2%) among the ESßLproducing uropathogens isolated in our sample. These findings are consistent with other studies that found a higher rate of ESβL production in K. pneumoniae (54.9%) than in E. coli (42.4%) 28 .…”
Section: Disscussionsupporting
confidence: 93%